Didaktik and Hermeneutics: On the Ontological Ground of the Art of Teaching and the Philosophical Nature of Didaktik - Adrian COSTACHE (Studia Universitatis Babeș-Bolyai. Philosophia)
This paper retraces the history of Didaktik and hermeneutics and argues that these two disciplines, seemingly unrelated at first, are deeply intertwined. The paper shows how Didaktik and hermeneutics first appeared in the 17th century, after a long period of gestation begun in Ancient Greece and carried further in the Middle Ages, as twin disciplines meant to address the basic needs of spiritual life. But it shows, their existence was short-lived, for they will disappear without a trace for more than a century only to be reborn again in the thought of Friedrich Schleiermacher under the impetus of the idea of alterity. This, the paper shows, will determine Schleiermacher to probe into the ontological ground of the act of teaching and will transform Didaktik, when understood in its full breadth, into a philosophical discipline.